Risk of postoperative bleeding following dental extractions in patients on antithrombotic treatment - Mohammed AlSheef; Jenny Gray; AbdulSalam AlShammari (Saudi Dental Journal)
Introduction: The risk of bleeding after dental extractions in patients taking antithrombotic medication is not well known. This study aims to investigate the incidence of postoperative bleeding following dental extractions in adult patients taking antithrombotic medication in Saudi Arabia. Methods: This retrospective study included 539 patients aged 18–93 years who attended 840 appointments for dental extractions from January 2012 to June 2016 at a tertiary care hospital in Saudi Arabia. Patients who returned with a complaint of bleeding were treated with local hemostatic measures as outpatients.Results and Conclusion: Only 1.7% of extraction appointments were associated with postoperative bleeding. The highest risk of bleeding was noted in patients receiving warfarin (3.88%), whereas those on clopidogrel had no significant risk of bleeding. Women were found to have the highest rate of bleeding, particularly those on newer oral anticoagulant medications.Dental extractions can be safely done in adults receiving antithrombotic treatment, provided established guidelines are followed; therefore, dental professionals must exercise caution when planning invasive dental treatment for patients on continued antithrombotic therapy.